Reporte de caso, fractura de tibia y peroné en un conejo doméstico (Oryctolagus cuniculus domesticus)” (2025)
The following report describes the clinical case of a 1year old male domestic rabbit, where the guardian reports that since the morning he sees that he hardly moves; The clinical examination revealed a fracture of the tibia and fibula of the right hind limb (MPD); It is recommended to take blood tests, take radiographs in Antero-posterior (AP) and right Lateral-Lateral (LLD) view